Peptides inhibiting Angiotensin I-converting enzyme derived from edible mushrooms / Lau Ching Ching - Lau, Ching Ching (2013)
Hypertension is one of the major health problems worldwide. Bioactive peptides that inhibit angiotensin I-converting enzyme (ACE) in the blood pressure regulation system (renin-angiotensin system) can contribute to the prevention and treatment of hypertension. Mushroom species studied are high in protein content, which makes them potentially a good source of antihypertensive peptides. Among the nine edible mushrooms evaluated, protein extracts from Pleurotus cystidiosus (E1Pc and E5Pc) and Agaricus bisporus (E1Ab and E3Ab) exhibited high levels of ACE inhibitory activity. The protein extracts were fractionated by reverse-phase high performance liquid chromatography (RPHPLC) into six fractions each. Fraction 3 from E5Pc (E5PcF3) and fraction 6 from E3Ab (E3AbF6) with the highest ACE inhibitory activity were selected for proteomic analysis. SDS-PAGE analysis showed E5PcF3 consisted mainly of low molecular weight proteins while E3AbF6 contained a variety of high to low molecular weight proteins. There were 22 protein clusters detected by SELDI-TOF-MS analysis with five common peaks found in E5PcF3 and E3AbF6, which had m/z values in the range of 3940 to 11413. Further purification by size exclusion chromatography (SEC) yielded seven fractions. SEC fraction 1 of E5PcF3 (E5PcF3C1) as well as SEC fraction 1 and 4 of E3AbF6 (E3AbF6C1 and E3AbF6C4) showed the highest percentages of ACE inhibitory activity. Nine peptides with potential ACE inhibitory activity were selected from the list of peptides obtained by LC/MS/MS analysis. Two peptides were from E5PcF3C1 (AHEPVK, GPSMR) while five peptides (KVAGPK, FALPC, RIGLF, EGEPR, APSAK) and three peptides (AHEPVK, GVQGPM, PSSNK) were selected from E3AbF6C1 and E3AbF6C4, respectively. The nine peptides were chemically synthesized and tested for their IC50 values and their stability against gastrointestinal enzymes (pepsin, trypsin and chymotrypsin). The lowest IC50 value was exhibited by AHEPVK, where 50% of ACE activity was reduced at a concentration of 62.6 μM. This iii was followed by RIGLF and PSSNK, where their IC50 values were 115.9 and 129.3 μM, respectively. Interestingly, the ACE inhibitory activity of the peptides was stable at the acidic and basic pH of stomach and intestine. Their biological activity was also retained after gastrointestinal digestion. BIOPEP analysis predicted AHEPVK was stable throughout the digestion process. The remaining eight peptides could be further hydrolyzed by the digestive enzymes to produce fragments of peptides, 2-4 amino acids in length with enhanced ACE inhibitory activity. The inhibition pattern of the three most potent peptides (AHEPVK, RIGLF and PSSNK) was determined by Lineweaver Burk plot. AHEPVK and RIGLF exhibited competitive inhibition pattern against the ACE while PSSNK showed noncompetitive inhibition pattern. Therefore, the peptides tested in the current study, particularly AHEPVK, RIGLF and PSSNK could be potential ACE inhibitors from mushroom. The widely available mushroom source and rare food allergy cases makes the peptides a potential source to be applied as ingredient in functional foods, dietary supplements or produced as pharmaceutical antihypertensive drugs.